Plant design on the production of coconut oil Sanchez method - Corpuz, Gilda J.; Gatchalian, Milagros H.; Mejia, Lydia A. (Diliman, Quezon City College of Engineering, 1977)
Plant: Coconut oil -- Location: Laguna -- Annual capacity at maximum rate of production: coconuts 39,600 tons, NaCl x^1 tab. 226 tons, NaOH (2° Baume) 28 tons, white coco oil 3,185 tons, yellow coco oil 451 tons, coconut protein 289 tons, coconut meal 1,149 tons, coconut water 8,580 tons, coconut shell 5,643 tons -- Fixed capital investments: P 11,693,470.00 -- Annual manufacturing cost at maximum capacity: Working days - 300 days/yr -- Break-even point: 39% capacity -- Shut-down point: 13% capacity -- Pay-out time: 2.4 years
Plant Design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Coconut oil